Differences In Raw Material Types On The Production Costs of Skin Crackers In Tengah Tani District - Rezkika Desmalia; Akhmad Saroji; Faizal Rifaldi; Siti Wahana (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2025)
Business actors often choose raw materials based on availability and price, without considering the total cost and overall product quality. This study aims to: (1) determine how the skin cracker production process for fresh, gareman and dried raw materials; (2) determine the contribution of raw material types to production process costs; and (3) determine the differences in raw material types on production costs. The hypothesis of this study is that there are suspected significant differences in the production costs of the skin cracker business based on the type of raw material used. The study was conducted in Tengah Tani District with purposive considerations with a research period from February to August 2025. The population of this study amounted to 16 business units, including 10 units using gareman raw materials, 3 units using fresh raw materials, and 3 units using dried raw materials. The research technique used a census technique so that the entire population was used as a sample and the data analysis technique used one-way ANOVA. The results of the study indicate that based on the selection of raw materials, more consideration is related to technical aspects. The largest contribution to raw material costs is garment raw materials. The total production costs based on differences in raw materials show differences with further analysis showing that production costsdrymuch lower than salted and fresh, but for salted and fresh, there was no statistically significant difference.